Successful hemostasis of an actively bleeding Dieulafoy’s lesion using only argon plasma coagulation in a patient with myelodysplastic syndrome and severe thrombocytopenia - Akar, Tarık (Turkish Journal of Gastroenterology, 2017)
Abstract Cite this article as: Akar T. Successful hemostasis of an actively bleeding Dieulafoy’s lesion using only argon plasma coagulation in a patient with myelodysplastic syndrome and severe thrombocytopenia. Turk J Gastroenterol 2017; 28: 423-4.